2010
DOI: 10.1111/j.1528-1167.2010.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Course and outcome of childhood epilepsy: A 15‐year follow‐up of the Dutch Study of Epilepsy in Childhood

Abstract: SUMMARYPurpose: To study the course and outcome of childhoodonset epilepsy during 15-year follow-up (FU). Methods: We extended FU in 413 of 494 children with new-onset epilepsy recruited in a previously described prospective hospital-based study by questionnaire. Results: Mean FU was 14.8 years (range 11.6-17.5 years). Five-year terminal remission (TR) was reached by 71% of the cohort. Course during FU was favorable in 50%, improving in 29%, and poor or deteriorating in 16%. Mean duration of seizure activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
190
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(228 citation statements)
references
References 35 publications
32
190
2
4
Order By: Relevance
“…30,31 In fact, learning problems were discussed as possibly contributing to poorer outcomes in 1 study. 32 They were also associated with adverse social outcomes in the Canadian cohort, although receipt of special education services was considered a poor outcome in that study. 1 Independent of seizure course, learning problems appear to impact several important adult outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 In fact, learning problems were discussed as possibly contributing to poorer outcomes in 1 study. 32 They were also associated with adverse social outcomes in the Canadian cohort, although receipt of special education services was considered a poor outcome in that study. 1 Independent of seizure course, learning problems appear to impact several important adult outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…38 We were generally not able to determine the onset of psychiatric problems relative to the onset of epilepsy, although learning problems clearly did precede the onset of epilepsy in many schoolaged children. 28 We also did not compare our cohort to the general population as done in some of the older studies, 2,5,32 which demonstrated differences in people with and without epilepsy. Our purpose was to distinguish the roles of seizures from behavioral and learning problems and identify factors within young people with epilepsy that might influence adult outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, for those who advocate the importance of promoting activity, the trial results were disappointing with relatively few between-group differences. 3,4 Despite a relatively intensive intervention with 30 sessions over 3 months, the group assigned to cycling did not show greater improvements in any of the measures of body structure and function, and activity than the control group. 4 For most quality of life…”
mentioning
confidence: 99%
“…It is difficult to verify these data since studies on deceased patients are by necessity retrospective and the clinical data may be scarce and inaccurate, both as to the circumstances of death as well as to the clinical details (especially after identification of such patients through the coroner's office). Here, the prospective nature of the cohort studies [1][2][3][4] compensates for their smaller number of deaths. From all studies on mortality in childhood epilepsy a clear picture now arises.…”
mentioning
confidence: 99%
See 1 more Smart Citation